Implementasi User Centered Requirements Engineering dalam Pencarian Kebutuhan Sistem eLearning - Deki Satria (Journal of Information System Research (JOSH), 2022)
Covid 19 pandemic force a lot of educational institution to shift their learning process from direct learning into indirect learning via eLearning. In fact, a lot of obstacle found when implementing effective eLearning system. This research use User Centered Requirement Engineering as methodology to find the system requirement based on the obstacle found. The main obstacles from this research are lack of interaction between the members of the eLearning, boredom and hard to fulfill the user expectations. The functional requirements to tackle this problem circle around the community functionality like comment and badge and the non-functional requirements mainly focused on the UI and UX of the systems.